Interaction studies of Gla-rich protein with bone morphogenetic proteins - Santos, Lúcia Alexandra Rosa dos (2014)
Cardiovascular disease is one of the main causes of death worldwide. Vascular calcification is a risk factor that strongly contributes to disease progression and to which the vitamin-K dependent family of proteins (VKDPs) appear to play a major role. Gla-rich protein, or GRP, was the last member of the VKDPs to be identified and has been associated with ectopic calcification in tissues such as skin, vasculature and cartilage in cases of dermatomyositis and pseudoxanthoma elasticum, chronic kidney disease and osteoarthritis, respectively, suggesting a possible role in the development and/or regulation of pathological calcification. Matrix Gla protein (MGP), another VKDP, is a recognized inhibitor of soft tissue calcification. Although its inhibitory mechanism is still not completely understood, distinct studies reported the binding of MGP to bone morphogenetic proteins (BMPs), known bone formation promoters in both skeletal and vascular tissue, antagonizing its function. However, these mechanisms of action are not enough to explain the numerous reported cases of calcification in humans leading us to hypothesize GRP as one of the missing regulators of calcification in soft tissues. Considering the reported data on MGP-BMP-2 interaction, and since an effect of BMP-2 on GRP expression has been previously demonstrated, we have focused in understanding the importance of GRP in calcification inhibition via interaction with MGP and BMP-2, either as a duplet or as a part of a larger protein complex. To further investigate these possibilities, we have engineered HEK293T cells to overexpress GRP and MGP and used their conditioned media in addition to recombinant BMP-2. Our immunoprecipitation assays demonstrate, for the first time, an interaction between GRP and BMP-2, supporting our hypothesis of GRP acting as a regulator of ectopic calcification via an interaction with BMP-2. Although our novel data indicate that GRP-BMP-2 interaction could be determining to vascular calcification, further functional studies will soon be performed to prove this hypothesis.